2020
DOI: 10.1101/2020.06.17.157404
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A DEAD BOX RNA helicase fromMedicago truncatulais hijacked by an RNA-binding effector from the root pathogenAphanomyces euteichesto facilitate host infection

Abstract: 26 Microbial effectors from plant pathogens are molecules that target host components to 27 facilitate colonization. While eukaryotic pathogens are virtually able to produce hundreds of 28 effectors, the molecular mechanisms allowing effectors to promote infection are still largely 29 unexplored. Here we show that the effector AeSSP1256 from the soilborne oomycete 30 pathogen Aphanomyces euteiches is able to interact with plant RNA. Heterologous expression 31 of AeSSP1256 delays Medicago truncatula host roots … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 84 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…SSPs have also been detected in A. astaci. Functional studies have shown that SSPs from A. euteiches can target plant nuclei and modify activity of plant DEAD-box RNA helicase to enhance A. euteiches infection (Camborde et al, 2020). These effectors appear to be a promising area of research to improve our understanding of the molecular factors involved in the virulence of A. euteiches.…”
Section: Intracellular Effectorsmentioning
confidence: 99%
“…SSPs have also been detected in A. astaci. Functional studies have shown that SSPs from A. euteiches can target plant nuclei and modify activity of plant DEAD-box RNA helicase to enhance A. euteiches infection (Camborde et al, 2020). These effectors appear to be a promising area of research to improve our understanding of the molecular factors involved in the virulence of A. euteiches.…”
Section: Intracellular Effectorsmentioning
confidence: 99%